Uncovering the Dynamics of Confined Water Using Neutron Scattering: Perspectives - Bordallo, Heloisa N.; Kneller, Gerald R. (Frontiers in Physics, 2022)
The main characteristic of liquid water is the formation of dynamic hydrogen bond networks that occur over a broad range of time scales from tens of femtoseconds to picoseconds and are responsible for water's unique properties. However, in many important processes water does not exist in its bulk form, but in confined nanometer scale environments. The investigation of this confined water dynamics is challenging since the intermediate strength of the hydrogen bonds makes it possible to alter the structure and dynamics of this constrained water. Even if no single experimental technique can give a full picture of such intricate dynamics, it is well established that quasielastic neutron scattering (QENS) is a powerful tool to study the modification of hydrogen bonds in confinement in various materials. This is possible because neutrons tell us where the atoms are and what they are doing, can detect hydrogen, are penetrative and non-destructive. Furthermore, QENS is the only spectroscopic technique that provides information on the dynamics and atomic-motion amplitudes over a predetermined length scale. However scientific value of these data is hardly exploited and never to its full potential. This perspective highlights how new developments on instrumentation and data analysis will lead to appreciable progress in our understanding of the dynamics of complex systems, ranging from biological organisms to cloud formation.